(untitled) (Research, Society and Development, 2023)
The objective of this work is to analyze the policies adopted by the government of the State of Goiás in the area of education during the period of sanitary restrictions caused by the Covid-19 pandemic, focusing on the 2020 school year. In particular, we will discuss the Special Class Regime (REANP) for students from the state network, offered through the official portal of the Goiás State Department of Education (SEDUC), pointing out the limits and possibilities of this model for quality education mediated by the use of Digital Technologies of Information and Communication (TDICs). The research carried out had an exploratory and bibliographic character. We evidenced the regularities, discrepancies and intensities of the actions and policies promoted during the period and published on the official SEDUC page. We conclude that there are many obstacles to universalization and the permanence of students in this teaching model mediated by the new DICTs and the context of sanitary restrictions. Social inequalities are the main limits of this policy, influencing the condition of who can or cannot follow teaching in this modality, which can interfere with the educational development of the state in the coming years. In addition, we highlight the possibilities of using the internet and new technologies to enhance basic education, building possibilities for literacy and digital literacy for students, teachers and educational managers. These possibilities should be explored more widely, allowing the offer of diversified content, the development of digital skills and competences and access to quality education for all students.